Pemberdayaan Peternak Sapi Melalui Program Corporate Social Responsibility Energy Equity Epic Kabupaten Wajo - Hikkal Ahmad Bayu (Jurnal Berita Sosial, 2022)
Model of empowerment of cattle farmers through the program (Corporate Social Responsibilty) Energy Equity Epic (Sengkang) Pty.Ltd and to determine the effectiveness of this program to empower cattle farmers in Gilireng District, Wajo Regency. This type of research is descriptive qualitative using a sociological approach that is indispensable in research as an effort to systematically identify and study social phenomena that exist in public relations. primary data sources obtained based on the results of interviews with informants and secondary data sources collected through relevant books and documents, the data collection methods used were observation, interviews, and documentation. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data display (data display), and drawing conclusions. The results of this study are that there are two models of cattle farmer empowerment used in this program, namely the Rolling Cattle Empowerment Model, and the Cattle Fattening Empowerment Model. The effectiveness of this program itself can be said to be successful, in addition to the objectives of this program being well implemented, the community also experienced an increase in the quality of life to be much better before joining this program. This is indicated by the increase in people’s income which has an effect on increasing the economy.